PENGARUH FAKTOR-FAKTOR INTERNAL TERHADAP PROFIT DISTRIBUTION MANAGEMENT (PDM) PADA BANK UMUM SYARIAH DI INDONESIA - Tri Utami; Sri Rezeqi (Universitas Pamulang, 2020)
This study aims to analyze the factors that affect the Profit Distribution Management (PDM) using the variable Proportion of Third Party Funds (PDPK), Provision for Earning Asset Losses (PPAP), Operational Cost of Operating Income (BOPO) and Financing Risk (RP) at Commercial Banks. Sharia in Indonesia. The period of this research is the first quarter of 2016 to the fourth quarter of 2018. This type of research is descriptive analysis with quantitative research methods. The data source used is in the form of secondary data and obtained from the Financial Services Authority (OJK) in the form of Islamic Commercial Bank (BUS) quarterly financial reports consisting of 12 Islamic Commercial Banks (BUS) from 2016 to 2018. The data used from these financial reports are reports Profit Sharing Distribution, Financial Position Report, Income Statement, Earning Asset Quality Report and Financial Ratio. The sampling technique used in this research is purposive sampling technique. This study uses panel data regression analysis using Eviews software version 9.5 The results of this study indicate that the Proportion of Third Party Funds (PDPK), Allowance for Earning Asset Losses (PPAP), Operational Cost of Operating Income (BOPO) and Financing Risk (RP) simultaneously affect the Profit Distribution Management (PDM). Meanwhile, partially, the proportion of third party funds (PDPK), operational costs operating income (BOPO) and financing risk (RP) have a significant negative effect on Profit Distribution Management (PDM). Meanwhile, Provision for Earning Asset Losses (PPAP) has no effect on Profit Distribution Management (PDM).